Composite powder with antibacterial function as well as preparation method and application of composite powder
By coating and modifying the powder slurry with ionic surfactant and antibacterial functional coupling agent, a composite powder with high antibacterial properties was prepared for the production of antibacterial SMC bathtubs, which solved the bathtubs in high humidity environments. The bacterial breeding problem has achieved efficient antibacterial effects and low-cost production.
Patent Information
- Application Number
- CN202411340039.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
Existing SMC bathtubs are prone to breed bacteria and mold in environments with high humidity and frequent use, resulting in hidden health risks and insufficient antibacterial performance.
The powder slurry is ground into mature slurry, mixed with ionic surfactant and then broken, and then coated with antibacterial functional coupling agent to prepare a composite powder with antibacterial function for the production of antibacterial SMC bathtub .
The antibacterial rate has reached 99.9%, effectively inhibiting bacterial growth and reproduction, providing a healthy and hygienic use environment, and the preparation method is simple and easy to implement, suitable for large-scale production, reducing production costs and improving production efficiency.
Smart Images

Figure FDA0005059423190000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of powder preparation, and in particular to a composite powder with antibacterial function and a preparation method and application thereof. Background Art
[0002] Bathtubs are common bathing facilities in households. Traditional bathtubs are mostly made of materials such as ceramic cast iron. These materials are prone to breed bacteria during long-term use, affecting people's health. With the development of science and technology, people have higher and higher requirements for the quality and function of bathtubs. As an innovative bathroom product, the antibacterial SMC bathtub has attracted much attention due to its lightness, beauty, environmental protection and excellent durability. However, the existing SMC bathtubs still have certain deficiencies in antibacterial aspects. Since the use environment of the bathtub is usually characterized by high humidity and frequent use, the bathtub is prone to breed bacteria and mold, which brings health risks to users. Therefore, antibacterial and antiseptic functions are essential for bathtubs. Summary of the invention
[0003] The purpose of the present invention is to provide a composite powder with antibacterial function and a preparation method and application thereof, so as to overcome the defects existing in the prior art.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a composite powder with antibacterial function, comprising the following steps:
[0006] (1) grinding the powder slurry to obtain a cooked slurry;
[0007] (2) mixing the cooked slurry and the ionic surfactant solution and breaking them up to obtain loose powder;
[0008] (3) The loose powder and the antibacterial functional coupling agent are mixed and coated and modified to obtain the composite powder with antibacterial function.
[0009] Preferably, the powder of the powder slurry in step (1) comprises calcium carbonate and wollastonite;
[0010] The mass ratio of calcium carbonate to wollastonite is 100:20-50;
[0011] The particle size of the powder in the powder slurry is 300-500 meshes.
[0012] Preferably, the solid content of the powder slurry in step (1) is 65-75%;
[0013] The grinding temperature in step (1) is 60-80° C.
[0014] The stirring speed of the grinding is 300-600 r / min.
[0015] Preferably, the particle size of the cooked slurry in step (2) is 800-1250 mesh;
[0016] The mass of the ionic surfactant in the ionic surfactant solution in step (2) is 0.5 to 1% of the mass of the cooked slurry;
[0017] The mass concentration of the ionic surfactant solution is 1-8%.
[0018] Preferably, the ionic surfactant is one or more of sodium dodecylbenzene sulfonate, ammonium dodecyl sulfate, benzalkonium chloride and benzalkonium bromide.
[0019] Preferably, the mixing temperature in step (2) is 70 to 90° C.
[0020] The mixing stirring speed is 400-600 r / min;
[0021] The mixing time is 50 to 70 minutes;
[0022] The speed of breaking up in the step (2) is 300-600 r / min;
[0023] The time for breaking up is 45 to 60 minutes.
[0024] Preferably, the mass ratio of the antibacterial functional coupling agent in step (3) to the powder in the powder slurry in step (1) is 0.5-0.8:100;
[0025] The structural formula of the antibacterial functional coupling agent is:
[0026] Wherein R is methyl or ethyl, and R1, R2 and R3 are independently alkyl, phenyl, ester or allyl.
[0027] Preferably, the coating modification temperature in step (3) is 80 to 120°C;
[0028] The coating modification time is 20 to 40 minutes.
[0029] The invention also provides a composite powder with antibacterial function prepared by the preparation method.
[0030] The present invention also provides application of the composite powder with antibacterial function in an SMC bathtub.
[0031] The present invention has the following beneficial effects:
[0032] 1. The present invention first grinds the powder slurry to obtain a cooked slurry, then mixes the cooked slurry with an ionic surfactant solution and breaks it up to obtain loose powder, and finally uses an antibacterial functional coupling agent to coat and modify the loose powder, thereby improving the compatibility of the powder and the resin system and giving the product good antibacterial properties, with an antibacterial rate of up to 99.9%.
[0033] 2. The bathtub made of the composite powder obtained by the present invention has excellent antibacterial properties, can effectively inhibit the growth and reproduction of bacteria, and provide users with a healthier and more hygienic use environment; the preparation method of the present invention is simple and easy, and large-scale production can be achieved through conventional industrial production equipment, which is conducive to reducing production costs and improving production efficiency.
[0034] 3. The composite powder obtained by the present invention is used to make SMC sheet molding compound, and the antibacterial SMC bathtub prepared therefrom has high strength and rigidity, can withstand a large amount of water and human weight, and is not easy to deform; it has excellent water resistance and is not easy to deform or crack after being immersed in water for a long time; the SMC bathtub matrix material has antibacterial function; it has a long service life and low maintenance cost. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a composite powder with antibacterial function, comprising the following steps:
[0036] (1) grinding the powder slurry to obtain a cooked slurry;
[0037] (2) mixing the cooked slurry and the ionic surfactant solution and breaking them up to obtain loose powder;
[0038] (3) The loose powder and the antibacterial functional coupling agent are mixed and coated and modified to obtain the composite powder with antibacterial function.
[0039] In the present invention, calcium carbonate and wollastonite are mixed and then crushed and ground in sequence to obtain dry powder.
[0040] In the present invention, the crushed particle size is preferably 800-1250 mesh, more preferably 850-1200 mesh, and even more preferably 900-1100 mesh.
[0041] In the present invention, the grinding rate is preferably 300 to 600 rpm, more preferably 350 to 550 rpm, and even more preferably 400 to 500 rpm.
[0042] In the present invention, dry powder and water are mixed to obtain powder slurry.
[0043] In the present invention, the powder of the powder slurry in step (1) preferably comprises calcium carbonate and wollastonite.
[0044] In the present invention, the mass ratio of calcium carbonate to wollastonite is preferably 100:20-50, more preferably 100:25-45, and even more preferably 100:30-40.
[0045] The particle size of the powder in the powder slurry is preferably 300-500 mesh, more preferably 330-470 mesh, and even more preferably 350-450 mesh.
[0046] In the present invention, the solid content of the powder slurry is preferably 65 to 75%, more preferably 67 to 73%, and even more preferably 68 to 72%.
[0047] In the present invention, the grinding temperature in step (1) is preferably 60 to 80°C, more preferably 62 to 78°C, and even more preferably 65 to 75°C.
[0048] In the present invention, the stirring speed of the grinding is preferably 300 to 600 r / min, more preferably 350 to 550 r / min, and even more preferably 400 to 500 r / min.
[0049] In the present invention, the particle size of the cooked slurry in step (2) is preferably 800-1250 mesh, more preferably 900-1150 mesh, and even more preferably 1000-1050 mesh.
[0050] In the present invention, the mass of the ionic surfactant in the ionic surfactant solution in step (2) is preferably 0.5-1% of the mass of the cooked slurry, more preferably 0.6-0.9%, and even more preferably 0.7-0.8%.
[0051] In the present invention, the mass concentration of the ionic surfactant solution is preferably 1 to 8%, more preferably 2 to 7%, and even more preferably 3 to 6%.
[0052] In the present invention, the ionic surfactant is preferably one or more of sodium dodecylbenzenesulfonate, ammonium dodecyl sulfate, benzalkonium chloride and benzalkonium bromide.
[0053] In the present invention, when two or more ionic surfactants are selected, their masses are preferably the same.
[0054] In the present invention, the mixing temperature in step (2) is preferably 70 to 90°C, more preferably 72 to 88°C, and even more preferably 75 to 85°C.
[0055] In the present invention, the stirring speed of the mixing is preferably 400 to 600 r / min, more preferably 430 to 570 r / min, and even more preferably 450 to 550 r / min.
[0056] In the present invention, the mixing time is preferably 50 to 70 min, more preferably 53 to 67 min, and even more preferably 55 to 65 min.
[0057] In the present invention, the cooked slurry and the ionic surfactant solution are mixed and then flash dried, collected and broken up in sequence to obtain loose powder.
[0058] In the present invention, the flash drying temperature is preferably 90 to 105°C, more preferably 92 to 103°C, and even more preferably 95 to 100°C.
[0059] In the present invention, the flash drying time is preferably 1 to 2 hours, more preferably 1.2 to 1.8 hours, and even more preferably 1.4 to 1.6 hours.
[0060] In the present invention, the speed of breaking up in step (2) is preferably 300 to 600 r / min, more preferably 350 to 550 r / min, and even more preferably 400 to 500 r / min.
[0061] In the present invention, the time for breaking up is preferably 45 to 60 min, more preferably 48 to 57 min, and even more preferably 50 to 55 min.
[0062] In the present invention, the purpose of breaking up is to maintain the original particle size of the loose powder particles.
[0063] In the present invention, the mass ratio of the antibacterial functional coupling agent in step (3) to the powder in the powder slurry in step (1) is preferably 0.5-0.8:100, more preferably 0.55-0.75:100, and more preferably 0.6-0.7:100.
[0064] In the present invention, the structural formula of the antibacterial functional coupling agent is preferably:
[0065] Wherein R is methyl or ethyl, and R1, R2 and R3 are independently alkyl, phenyl, ester or allyl.
[0066] In the present invention, the preparation method of the antibacterial functional coupling agent comprises the following steps:
[0067] The antibacterial functional coupling agent is obtained by mixing an aminosilane coupling agent, a halogenated hydrocarbon, water and a catalyst for reaction.
[0068] In the present invention, the molar ratio of the aminosilane coupling agent to the halogenated hydrocarbon is preferably 1:3-5, more preferably 1:3.5-4.5, and even more preferably 1:3.8-4.2.
[0069] In the present invention, the mass ratio of the aminosilane coupling agent to the halogenated hydrocarbon and to water is preferably 1:2-5, more preferably 1:2.5-4.5, and even more preferably 1:3-4.
[0070] In the present invention, the mass of the catalyst is preferably 1-10% of the total mass of the aminosilane coupling agent and the halogenated hydrocarbon, more preferably 2-8%, and even more preferably 4-6%.
[0071] In the present invention, the catalyst is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.
[0072] In the present invention, the reaction temperature is preferably 80-100°C, more preferably 85-95°C, more preferably 88-92°C; the reaction time is preferably 5-24h, more preferably 10-20h, more preferably 14-16h; the stirring speed is preferably 500-600rpm, more preferably 520-580rpm, more preferably 540-560rpm.
[0073] In the present invention, the coating and modification process is to spray the antibacterial functional coupling agent during the stirring of the loose powder.
[0074] In the present invention, the stirring rate is preferably 300 to 600 r / min, more preferably 350 to 550 r / min, and more preferably 400 to 500 r / min.
[0075] In the present invention, the temperature of the coating modification in step (3) is preferably 80 to 120°C, more preferably 85 to 115°C, and even more preferably 90 to 110°C.
[0076] In the present invention, the coating modification time is preferably 20 to 40 minutes, more preferably 24 to 36 minutes, and even more preferably 28 to 32 minutes.
[0077] In the present invention, the coated and modified powder is sieved to obtain the composite powder with antibacterial function.
[0078] The invention also provides a composite powder with antibacterial function prepared by the preparation method.
[0079] The present invention also provides application of the composite powder with antibacterial function in an SMC bathtub.
[0080] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0081] Example 1
[0082] Calcium carbonate and wollastonite were mixed in a mass ratio of 100:30 and crushed to 900 mesh. The crushed material was then ground into 400 mesh dry powder at a speed of 400 rpm. The dry powder was mixed with water to form a powder slurry with a solid content of 70%, which was pumped into a 3600L wet grinder and wet-ground at 65°C at a stirring speed of 400 r / min to form a cooked slurry with a particle size of 800 mesh.
[0083] Ammonium dodecyl sulfate and benzalkonium chloride are mixed with water in a mass ratio of 1:1 to prepare an ionic surfactant solution with a mass concentration of 5%. The ammonium dodecyl sulfate and benzalkonium chloride are mixed with the cooked slurry in a ratio of 0.5% of the mass of the cooked slurry at 80°C and a stirring speed of 500 r / min for 60 minutes, and then flash dried at 100°C for 1.5 hours. The dried powder is collected in a cloth bag and added to a disperser for depolymerization and dispersion at a speed of 400 r / min for 50 minutes to obtain loose powder.
[0084] The loose powder is stirred at a rate of 400r / min, and an antibacterial functional coupling agent is sprayed during the stirring process (the mass ratio of the antibacterial coupling agent to the powder in the powder slurry is 0.8:100; R in the antibacterial coupling agent is methyl, and R1, R2, and R3 are ethyl. The preparation method is as follows: the aminosilane coupling agent and the halogenated hydrocarbon are mixed in a molar ratio of 1:3, and then water 3 times the total mass of the first two is added, accounting for the mass of the coupling agent and the halogenated hydrocarbon and 5% of sodium hydroxide, and the reaction is carried out at 90°C and 550rpm for 15h to obtain the antibacterial coupling agent.) The coating modification is carried out at 100°C for 30min, and the coated and modified powder is sieved to obtain a composite powder with antibacterial function.
[0085] The unsaturated polyester resin, glass fiber and the composite powder obtained in this example were mixed in a mass ratio of 100:30:80 to prepare an SMC sample, the tensile strength of which was 33 MPa and the antibacterial rate reached 99.9%.
[0086] Example 2
[0087] Calcium carbonate and wollastonite were mixed in a mass ratio of 100:50 and crushed to a particle size of 800 mesh. The crushed material was then ground into a dry powder of 400 mesh at a speed of 600 rpm. The dry powder was mixed with water to form a powder slurry with a solid content of 70%, which was pumped into a 3600L wet grinder and wet-ground at 75°C at a stirring speed of 500 r / min to form a cooked slurry with a particle size of 800 mesh.
[0088] Ammonium dodecyl sulfate was mixed with water to prepare an ionic surfactant solution with a mass concentration of 5%. The ammonium dodecyl sulfate was mixed with the cooked slurry at a ratio of 0.5% of the mass of the cooked slurry at 80°C and a stirring speed of 500 r / min for 60 min. The mixture was flash dried at 95°C for 1.5 h. The dried powder was collected in a cloth bag and added to a disperser for depolymerization and dispersion at a speed of 400 r / min for 50 min to obtain loose powder.
[0089] The loose powder is stirred at a rate of 500r / min, and an antibacterial functional coupling agent is sprayed during the stirring process (the mass ratio of the antibacterial coupling agent to the powder in the powder slurry is 0.8:100; R in the antibacterial coupling agent is ethyl, and R1, R2, and R3 are phenyl. The preparation method is as follows: the aminosilane coupling agent and the halogenated hydrocarbon are mixed in a molar ratio of 1:4, and then water 5 times the total mass of the first two is added, and potassium hydroxide accounting for 10% of the mass of the coupling agent and the halogenated hydrocarbon is added, and the reaction is carried out at 80°C and 500rpm for 20h to obtain the antibacterial coupling agent.) The coating modification is carried out at 100°C for 30min, and the coated and modified powder is sieved to obtain a composite powder with antibacterial function.
[0090] The unsaturated polyester, glass fiber and the composite powder obtained in this example were mixed in a mass ratio of 100:30:80 to prepare an SMC sample, the tensile strength of which was 36 MPa and the antibacterial rate reached 99.9%.
[0091] The epoxy resin, glass fiber and the composite powder obtained in this example were mixed in a mass ratio of 100:30:80 to prepare an SMC sample, the tensile strength of which was 40 MPa and the antibacterial rate reached 99.9%.
[0092] Example 3
[0093] Calcium carbonate and wollastonite were mixed in a mass ratio of 100:30 and crushed to a particle size of 1200 mesh. The crushed material was then ground into a dry powder of 400 mesh at a speed of 500 rpm. The dry powder was mixed with water to form a powder slurry with a solid content of 70%, which was pumped into a 3600L wet grinder and wet-ground at 60°C at a stirring speed of 300 r / min to form a cooked slurry with a particle size of 800 mesh.
[0094] Ammonium dodecyl sulfate was mixed with water to prepare an ionic surfactant solution with a mass concentration of 5%. The ammonium dodecyl sulfate was mixed with the cooked slurry at a ratio of 0.5% of the mass of the cooked slurry at 80°C and a stirring speed of 500 r / min for 60 min. The mixture was flash dried at 90°C for 1 h. The dried powder was collected in a cloth bag and added to a disperser for depolymerization and dispersion at a speed of 300 r / min for 45 min to obtain loose powder.
[0095] The loose powder is stirred at a rate of 300 r / min, and an antibacterial functional coupling agent is sprayed during the stirring process (the mass ratio of the antibacterial coupling agent to the powder in the powder slurry is 0.8:100; R in the antibacterial coupling agent is methyl, and R1, R2, and R3 are phenyl. The preparation method is as follows: the aminosilane coupling agent and the halogenated hydrocarbon are mixed at a molar ratio of 1:5, and then water 5 times the total mass of the first two is added, and sodium carbonate accounting for 8% of the mass of the coupling agent and the halogenated hydrocarbon is added, and the reaction is carried out at 100°C and 580rpm for 12 hours to obtain the antibacterial coupling agent.) The coating modification is carried out at 100°C for 30 minutes, and the coated and modified powder is sieved to obtain a composite powder with antibacterial function.
[0096] The epoxy resin, glass fiber and the composite powder obtained in this example were mixed in a mass ratio of 100:30:80 to prepare an SMC sample, the tensile strength of which was 38 MPa and the antibacterial rate reached 99.9%.
[0097] As can be seen from the above embodiments, the present invention provides a method for preparing a composite powder with antibacterial function, comprising the following steps: grinding a powder slurry to obtain a cooked slurry, mixing the cooked slurry with an ionic surfactant solution and breaking it up to obtain loose powder, and finally coating and modifying the loose powder with an antibacterial functional coupling agent, thereby improving the compatibility of the powder with the resin system and giving the product good antibacterial properties; a bathtub made of the composite powder obtained by the present invention has excellent antibacterial properties, can effectively inhibit the growth and reproduction of bacteria, and provide a healthier and more hygienic use environment for users; the preparation method of the present invention is simple and easy, and large-scale production can be achieved through conventional industrial production equipment, which is conducive to reducing production costs and improving production efficiency; the composite powder obtained by the present invention is used to make SMC sheet molding compound, and the antibacterial SMC bathtub prepared thereby has high strength and rigidity, can withstand a large amount of water and human weight, is not easy to deform, and has a tensile strength of up to 40MPa; has excellent water resistance, and is not easy to deform or crack when immersed in water for a long time; the SMC bathtub matrix material has an antibacterial function, and the antibacterial rate reaches 99.9%; has a long service life and low maintenance cost.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite powder with antibacterial function, characterized in that: It includes the following steps: (1) grinding the powder slurry to obtain a cooked slurry; (2) mixing the cooked slurry and the ionic surfactant solution and breaking them up to obtain loose powder; (3) The loose powder and the antibacterial functional coupling agent are mixed and coated to obtain the composite powder with antibacterial function.
2. The preparation method according to claim 1, characterized in that: The powder of the powder slurry in step (1) comprises calcium carbonate and wollastonite; The mass ratio of calcium carbonate to wollastonite is 100:20-50; The particle size of the powder in the powder slurry is 300-500 meshes.
3. The preparation method according to claim 1, characterized in that: The solid content of the powder slurry in step (1) is 65-75%; The grinding temperature in step (1) is 60-80° C. The stirring speed of the grinding is 300-600 r / min.
4. The preparation method according to claim 1, characterized in that: The particle size of the cooked slurry in step (2) is 800-1250 mesh; The mass of the ionic surfactant in the ionic surfactant solution in step (2) is 0.5 to 1% of the mass of the cooked slurry; The mass concentration of the ionic surfactant solution is 1-8%.
5. The preparation method according to claim 4, characterized in that: The ionic surfactant is one or more of sodium dodecylbenzene sulfonate, ammonium dodecyl sulfate, benzalkonium chloride and benzalkonium bromide.
6. The preparation method according to claim 1, characterized in that: The mixing temperature in step (2) is 70 to 90° C. The mixing stirring speed is 400-600 r / min; The mixing time is 50 to 70 minutes; The speed of breaking up in the step (2) is 300-600 r / min; The time for breaking up is 45 to 60 minutes.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the antibacterial functional coupling agent in step (3) to the powder in the powder slurry in step (1) is 0.5-0.8:100; The structural formula of the antibacterial functional coupling agent is: Wherein R is methyl or ethyl, and R1, R2 and R3 are independently alkyl, phenyl, ester or allyl.
8. The preparation method according to claim 1, characterized in that: The coating modification temperature in step (3) is 80 to 120°C; The coating modification time is 20 to 40 minutes.
9. The composite powder with antibacterial function prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the composite powder with antibacterial function as claimed in claim 9 in a SMC bathtub.